2021
DOI: 10.3389/fnagi.2021.748888
|View full text |Cite|
|
Sign up to set email alerts
|

Liver Health and Dementia in an Italian Older Population: Findings From the Salus in Apulia Study

Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) currently affects a quarter of the global population. Systemic inflammation, metabolic syndrome, and coronary artery disease, all conditions associated with NAFLD, have also been related to cognitive dysfunction in older age. The present study aimed to investigate the relationship between NAFLD risk and a dementia diagnosis in a large population-based sample aged > 65 years.Methods: We selected 1,542 participants (723 men) from the Salus in Apulia St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
1
12
0
1
Order By: Relevance
“…Of these 9 articles, 8 failed to provide relevant data and outcomes and 1 article provided incomplete data. Ultimately, 7 studies (Labenz et al, 2021 ; Lampignano et al, 2021 ; Shang et al, 2021 ; Jeong et al, 2022 ; Kim et al, 2022 ; Liu et al, 2022 ; Yu et al, 2022 ) were included in this study. The search selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 9 articles, 8 failed to provide relevant data and outcomes and 1 article provided incomplete data. Ultimately, 7 studies (Labenz et al, 2021 ; Lampignano et al, 2021 ; Shang et al, 2021 ; Jeong et al, 2022 ; Kim et al, 2022 ; Liu et al, 2022 ; Yu et al, 2022 ) were included in this study. The search selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were included in this review. Five studies (Labenz et al, 2021 ; Shang et al, 2021 ; Jeong et al, 2022 ; Kim et al, 2022 ; Liu et al, 2022 ) were cohort studies and 2 studies (Lampignano et al, 2021 ; Yu et al, 2022 ) were case–control studies. The 7 studies were published from 2020 to 2022 and involved a total of 891,562 individuals, with sample sizes ranging from 1542 to 608,994 individuals per study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD is the most common cause of chronic liver disease in Western countries [ 90 ]. Many risk factors have been associated with cardiovascular disease [ 91 ], but only a few studies have investigated the association between NAFLD and a risk of dementia.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…In a study by Lampignano et al from 2021, they found that an index score developed to predict the risk of NAFLD was associated with a higher risk of all-cause dementia [ 90 ]. Another study that included 646 NAFLD cases did not find an association between NAFLD and a risk of dementia, however, when integrating fibrosis stage in a risk prediction model with conventional risk factors, they found an improved prediction of dementia risk [ 94 ].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%